Pharmacological inhibition to examine the role of DGAT1 in dietary lipid absorption in rodents and humans - Maciejewski, Benjamin S.; LaPerle, Jennifer L.; Chen, Danny; Ghosh, Avijit; Zavadoski, William J.; McDonald, Thomas S.; Manion, Tara B.; Mather, Dawn; Patterson, Terrell A.; Hanna, Maya; Watkins, Steven; Gibbs, E. Michael; et al. (American journal of physiology: Gastrointestinal and liver physiology, 2013)
Alterations in fat metabolism, in particular elevated plasma concentrations of free fatty acids and triglycerides (TG), have been implicated in the pathogenesis of Type 2 diabetes, obesity, and cardiovascular disease. Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1), a member of the large family of membrane-bound O-acyltransferases, catalyzes the final step in triacylglycerol formation. In the intestine, DGAT1 is one of the acyltransferases responsible for the reesterficiation of dietary TG. Following a single dose of a selective pharmacological inhibitor of DGAT1, PF-04620110, a dose-dependent inhibition of TG and vitamin A absorption postprandially was demonstrated in rodents and human subjects. In C57/BL6J mice, acute DGAT1 inhibition alters the temporal and spatial pattern of dietary lipid absorption. To understand the impact of DGAT1 inhibition on enterocyte lipid metabolism, lipomic profiling was performed in rat intestine and plasma as well as human plasma. DGAT1 inhibition causes an enrichment of polyunsaturated fatty acids within the TG class of lipids. This pharmacological intervention gives us insight as to the role of DGAT1 in human dietary lipid absorption.